Identifikasi Zona Lemah Tanggul Daerah Aliran Sungai (DAS) Bumang Desa Kemuja Menggunakan Metode Geolistrik Resistivitas Konfigurasi Wenner - Amelia, Dea; Widyaningrum, Yekti; Indriawati, Anisa (Jurnal Riset Fisika Indonesia, 2024)
The Bumang Watershed is a stream of water originating from the Bumang Reservoir in Kemuja Village, Bangka Regency to hold back water from flooding the surrounding rice fields. Since the Bumang watershed embankment was built, the embankment has been damaged in the upper part of the Bumang watershed. The main cause is underground erosion. The erosion caused the embankment foundation to become weak, which was identified as a weak zone. The method used to identify weak zones in the embankment is the Wenner configuration resistivity geoelectric method. The Wenner configuration has good sensitivity to lateral changes compared to other configurations. Field data acquisition consisted of four passes with different electrode lengths and spacings. Based on the 2D cross-section of the subsurface of the Bumang watershed embankment, the weak zone is located on tracks 1, 2, and 3. On track 1 it is at a depth of 2.50 m - 3.19 m and 1.30 m - 3.19 m; on track 2 it is at a depth of 0 m - 2 m; and on track 3 it is at a depth of 0 m - 7 m, 2 m - 4.50 m, and 0 m - 4 m respectively.